2019
DOI: 10.2903/j.efsa.2019.5664
|View full text |Cite
|
Sign up to set email alerts
|

Avian influenza overview November 2018 – February 2019

Abstract: No human infections due to highly pathogenic avian influenza (HPAI) A(H5N8) or A(H5N6) viruses ‐ detected in wild birds and poultry outbreaks in Europe ‐ have been reported so far and the risk of zoonotic transmission to the general public in Europe is considered very low. Between 16 November 2018 and 15 February 2019, two HPAI A(H5N8) outbreaks in poultry establishments in Bulgaria, two HPAI A(H5N6) outbreaks in wild birds in Denmark and one low pathogenic avian influenza (LPAI) A(H5N3) in captive birds in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 60 publications
1
3
0
Order By: Relevance
“…Here, the first H5N6 clade 2.3.4.4.b introduction into Africa from Europe, most likely via wild birds is reported. HPAI H5N6 bearing the same gene constellation of the Nigerian strain, had already caused a total of 98 outbreaks in Europe between late-2017 and early 2019, of which 92% had occurred in wild birds [12]. This finding confirms our previous study, which recognized West Africa, and in particular Nigeria, as one of the most important hotspot for Gs/GD/96 HPAI H5Nx introduction into Africa [5].…”
supporting
confidence: 87%
“…Here, the first H5N6 clade 2.3.4.4.b introduction into Africa from Europe, most likely via wild birds is reported. HPAI H5N6 bearing the same gene constellation of the Nigerian strain, had already caused a total of 98 outbreaks in Europe between late-2017 and early 2019, of which 92% had occurred in wild birds [12]. This finding confirms our previous study, which recognized West Africa, and in particular Nigeria, as one of the most important hotspot for Gs/GD/96 HPAI H5Nx introduction into Africa [5].…”
supporting
confidence: 87%
“…During the 2020-2021 and 2021-2022 outbreaks of high pathogenicity avian influenza in the UK, there has been an increased detection of HPAIV H5N1 in seabirds of the Orders Suliformes and Laridae. 3,6,16,34 This investigation of naturally acquired infection revealed that gross pathology was limited to pancreatic necrosis in the herring gull and proventricular ulceration in the great skua. The pancreatic changes were less characteristic compared to that in Galliformes and Anseriformes and required immunohistochemical confirmation.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the last report, no case of HPAI A(H5N2) was reported to the OIE between 16 August and 25 November. The Taiwanese lineages of HPAI A(H5N2) (clade 2.3.4.4) differ from the Eurasian HPAI A(H5N2) lineage (Li et al, 2020); the latter belonging to clade 2.3.4.4b, which has been detected, with different genotypes, in Egypt and Russia as well as in Asian countries between 2016 and 2019 (EFSA et al, 2019a) and in Bulgaria in 2020.…”
Section: Detectionsmentioning
confidence: 97%